EFFECTIVENESS OF FUNGICIDAL CONTROL OF DOMINANT TOMATO DISEASES - Pospielova, G. D.; Kovalenko, N. P.; Nechyporenko, N. I.; Pospielov, S. V.; Poliakov, I. A.; Tur, V. Y. (Scientific Progress & Innovations, 2020)
The peculiarities of spreading and developing Altenaria blight (Alternaria solani) and Phytophthora rot (Phytophthora infestans) on plants of Raspberry Vicante tomatoes during the growing season in 2019–2020 on production plantations were studied. The influence of hydrothermal conditions on spreading and develop-ing dominant tomato diseases in the Forest-Steppe zone of Ukraine was determined. It has been noted that weather conditions of 2019 (the alternation of hot dry weather with rains and abundant dews) contributed to Alternaria blight spreading: 12.3 % in flowering phase and 26.3 % in fruiting phase. Moreover, the intensity of the disease development during fruit formation reached a maximum value of 32.3 %, which was 12.5 % higher than in the flowering phase. In order to control Alternaria blight and Phytophthora rot on tomatoes of Raspberry Vicante variety, the effect of different chemical group fungicides were studied. Rydomil Gold MC 680 g/l WG preparation (metalaxyl-M, 40 g/kg + mancoceb, 640 g/kg) was chosen as a standard, the effectiveness of which was compared with more modern preparations: Cabrio Duo, 112 g/l k.e. (pyra-clostrobin, 40 g/l + dimetomorph, 72 g/l) and Concento, 450 g/l k.e. (phenamidone 75 g/l + propamocarb hydrochloride, 375 g/l). The studied fungicides were characterized by high fungistatic activity, but the causa-tive agents of Alternaria blight and Phytophthora rot showed different sensitivity to the active substances. Cabrio Duo, 112 g/l k.e. (suppressed the disease development by 78.5 %) and Concento, 450 g/l k.e. (sup-pressed the disease development by 85.2 %) were more effective in comparison to the standard preparation Rydomil Gold, 680 g/l v.g. for the protection of plants against Phytophthora rot. The similar effect was ob-served for Alternaria blight: Cabrio Duo, 112 g/l k.e, was the most effective with technical efficacy of 83.4 %. This indicator was 23.6 % higher than the standard. The effectiveness of Consento fungicide, 450 g/l k.s. was slightly lower (4.5 %) than that of Cabrio Duo, 112 g/l k.e., but it was 28.1 % higher in comparison with Rydomil Gold fungicide, 680 g/l v.g. (59.8 %). The conducted studies confirm the specific activity of selected fungicides against diseases caused by lower (Phytophthora infestans) and higher (Alter-naria solani) fungi. Analyzing the composition of complex of active substances of the two studied prepara-tions, it has been assumed that mentioned specificity is ensured by a combination of two active substances: pyraclostrobin and dimetomorph for Cabrio Duo; and phenamidone and propamocarb hydrochloride for Consento. A slightly lower effectiveness of Cabrio Duo as compared with Consento may indicate the development of resistance in the population of Phytophthora rot causative agent to strobilurin. Concento showed a synergistic effect of active substances which increased the total fungi-toxic effect of the preparation and, thus, its technical efficacy. A relatively low technical effectiveness of Rydomil Gold may be associated with the development of resistance of Phytophthora rot and Alternaria blight causative agent to metalaxyl-M and mancoceb.